2006
DOI: 10.1111/j.1365-2583.2005.00605.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiles underlying alternative caste phenotypes in a highly eusocial bee, Melipona quadrifasciata

Abstract: To evaluate caste-biased gene expression in Melipona quadrifasciata, a stingless bee, we generated 1278 ESTs using Representational Difference Analysis. Most annotated sequences were similar to honey bee genes of unknown function. Only few queen-biased sequences had their putative function assigned by sequence comparison, contrasting with the worker-biased ESTs. The expression of six annotated genes connected to caste specificity was validated by real time PCR. Interestingly, queens that were developmentally i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 74 publications
2
53
0
Order By: Relevance
“…This way, four subtractive cDNA libraries were generated, two representing genes that are overexpressed in mucus glands of newly emerged (NE) drones and two for 8 day-old (8d) drones. The methodology employed was a cDNA Representational Difference Analysis (RDA) (Pastorian et al, 2000) adapted for applications in bees (Judice et al, 2006). For the NE libraries, cDNA of newly emerged drones served as the tester population that was hybridized against cDNA of the 8d library as the driver population.…”
Section: Representational Difference Analysis (Rda)mentioning
confidence: 99%
“…This way, four subtractive cDNA libraries were generated, two representing genes that are overexpressed in mucus glands of newly emerged (NE) drones and two for 8 day-old (8d) drones. The methodology employed was a cDNA Representational Difference Analysis (RDA) (Pastorian et al, 2000) adapted for applications in bees (Judice et al, 2006). For the NE libraries, cDNA of newly emerged drones served as the tester population that was hybridized against cDNA of the 8d library as the driver population.…”
Section: Representational Difference Analysis (Rda)mentioning
confidence: 99%
“…The Representational Difference Analysis (RDA) is a version of a suppression subtractive hybridization strategy, and it was used to generate two libraries enriched for queen and for worker transcripts, respectively. This approach generated 1278 high quality ESTs, representing 337 unique sequences (Judice et al, 2006). As in the DDRT-PCR study on caste-specific gene expression in Melipona, this approach also revealed a much broader functional spectrum of transcripts in the worker library (22 unique sequences with exclusive occurrence in workers, versus 5 exclusive to queens).…”
Section: From Caste To Blast: Differential Gene Expression In Meliponmentioning
confidence: 99%
“…Up to now, however, none of the many studies investigating JH action in stingless bees really gave a conclusive answer to this question, because JH-induced queens apparently have problems in establishing colonies. Based on recent evidence we consider the lack in queenlike behavior in JH-induced queens as a physiological phenomenon because of the surprisingly high divergence in gene expression patterns for JH-induced queens when compared to newly emerged natural queens (Judice et al, 2006; and see below Sect. 2.4).…”
Section: Melipona a Special Case?mentioning
confidence: 99%
“…(ii) The transcriptional basis of the wing dimorphisms Transcriptional profiling of polyphenisms via microarrays, cDNA sequencing, subtractive hybridization and (at least in the very near future) RNA sequencing is becoming an accessible form of investigation in nonmodel systems, and has been used to characterize the gene-expression states of alternative morphologies in termites (Scharf et al 2003), bees (Evans & Wheeler 1999;Pereboom et al 2005;Judice et al 2006), parasitic wasps (Donnell & Strand 2006) and social wasps (Hoffman & Goodisman 2007). A particular advantage of gene-expression profiling in the aphid wing polyphenism is that the confounding effect of genotype can be controlled by using aphids of the same clone.…”
Section: Towards An Understanding Of the Molecular Genetic Basis Of Tmentioning
confidence: 99%